2019
DOI: 10.1177/2096595819896200
|View full text |Cite
|
Sign up to set email alerts
|

Ten challenges for EEG-based affective computing

Abstract: The emerging field of affective computing focuses on enhancing computers’ ability to understand and appropriately respond to people’s affective states in human-computer interactions, and has revealed significant potential for a wide spectrum of applications. Recently, the electroencephalography (EEG) based affective computing has gained increasing interest for its good balance between mechanistic exploration and real-world practical application. The present work reviewed ten theoretical and operational challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 139 publications
(169 reference statements)
0
40
0
Order By: Relevance
“…The phenomena of coexistence should be considered in affective tagging. We recommend that future studies should focus on two issues to develop a more accurate affective definition and conduct better forecasting: (1) they should aim for a deeper understanding of consumer ambivalence, characterized by the co-occurrence of positive and negative emotions (Kreibig and Gross, 2017;Hu et al, 2019); and (2) consider emotion dyads, namely, a mix of primary emotions, raised by Plutchik (1980). The multidimensional and multimodal feature fusion can obtain better recognition performance.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomena of coexistence should be considered in affective tagging. We recommend that future studies should focus on two issues to develop a more accurate affective definition and conduct better forecasting: (1) they should aim for a deeper understanding of consumer ambivalence, characterized by the co-occurrence of positive and negative emotions (Kreibig and Gross, 2017;Hu et al, 2019); and (2) consider emotion dyads, namely, a mix of primary emotions, raised by Plutchik (1980). The multidimensional and multimodal feature fusion can obtain better recognition performance.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed previously, several studies have shown that including EEG features considerably improves the classification accuracy. However, there are several challenges in using EEG for emotion recognition [ 126 ], including the selection of robust features, continous decoding of affective states, reliable decoding of long-term reliability of EEG recordings for such studies, long preparation time, and, most importantly, adopting a proper model of emotion with regard to EEG and understanding the EEG representation of affective states. For an excellent overview of these challenges the reader is directed to [ 126 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, here we relied on the participants’ self-evaluation of their state-level mood and creativity. Given the rapid development of wearable bio-sensing technologies and machine learning methods [ 70 72 ], it is expected to have a momentary evaluation of one’s state creativity and mood states in an objective way that could further our understanding of the mood-creativity link. Last but not least, while the mood states were categorized into positive and negative moods, it might be necessary to have a more fine-grained categorization.…”
Section: Discussionmentioning
confidence: 99%